Reinstatement of the genus Capicua Navás with descriptions of two new species (Neuroptera, Myrmeleontidae) - Michel, Bruno; Akoudjin, Massouroudini (Zootaxa, 2011)
The genus Capicua Navás, 1921, synonymised with Geyria Esben-Petersen, 1920 by Stange (2004), is reinstated and redescribed. The unique specimen of Capicua fulvicauda Navás, 1921 kept in the Muséum d’Histoire Naturelle, Paris is designated as lectotype. Two new species of antlions from West Africa are described and tentatively included in Capicua pending more material of the type species C. fulvicauda to verify this placement. Holotypes and paratypes are deposited in the collection of CIRAD/CBGP in Montpellier, France.